A novel composite retanning system based on pH-responsive hydrogen bonding and hydrophobic interaction for cleaner leather processing. (10th March 2022) - Zhou, Rong; Jin, Yong; Lai, Shuangquan; Shi, Liangjie; Bai, Long; Peng, Zhangyi
Abstract: Aldehyde-tanned leather is one of the promising choices to avoid the widespread chrome pollution in leather industry. However, due to the lack of metal ions, the aldehyde-tanned leather faces a significant challenge of not being able to effectively fix traditional anionic retanning materials, which seriously affects the quality of aldehyde-tanned leather. Herein, a novel composite retanning system consisting of arylic resin (AR) and F6-600 (a nonionic fluorinated surfactant with poly(ethylene oxide) (PEO)) was constructed, which breaks through the dependence of conventional leather materials on metal ions in terms of fixation. The main acting mechanism is that at the final stage of retanning, after reducing the float pH, pH-responsive hydrogen bonding and hydrophobic interaction synergistically drive AR/F6-600 to self-assemble into bigger polymer composite aggregates, and then these aggregates are forced to deposit and fill in leather fiber gaps, thus obtaining more desirable retanning results. Furthermore, AR/F6-600 composite retanning system is eco-friendly. The AR/F6-600 retanned leather has lower free formaldehyde content, better biodegradability, and higher uptake rates for subsequent dye and fatliquoring agent, which can further eliminate the threat of formaldehyde to health, accelerate the degradation of waste leather in the nature, and reduce the chemical residual in wastewater, respectively. Consequently, this novel retanning system will benefit to satisfy evolving demands for related technologies toward cleaner leather production. Graphical abstract: Image 1 Highlights: AR/F6-600 retanning system was built by hydrogen bonding and hydrophobic interaction. The system breaks the dependence of fixing traditional retanning agent on metal ions. AR/F6-600 reduces the content of free formaldehyde in aldehyde-tanned leather. AR/F6-600 is favorable for biodegradability, dying and fatliquoring of leather. F6-600 and the extracts from the AR/F6-600 retanned leather are non-cytotoxicity.